Science Process Skills Improvement through Cooperative Model Type Jigsaw on Students of Class IV-B MI Darun Najah Kloposepuluh - Faizah, Rohmatul (Indonesian Journal of Science Learning (IJSL), 2020)
The results of the observation on the students of class IV-B MI Darun Najah Kloposepuluh Sidoarjo shows that the science process skills was still low, especially in theme 5 sub-theme 1 learning 1. The results of interviews with classroom teachers obtained information that the lecture method is often used in teaching so that students are less active in learning. One of the efforts to encourage the active participation of students in learning is by applying cooperative learning model type Jigsaw. This study aims to determine the implementation of cooperative learning type Jigsaw in order to improve the students’ science process skills of Class IV-B Darun Najah Kloposepuluh and determine the increase of science process skills using cooperative model type Jigsaw on students of class IV-B MI Darun Najah Kloposepuluh Sidoarjo. The research method used was Classroom Action Research (CAR) with the model of Kurt Lewin, which held as much as two cycles. The results showed that (1) the application of cooperative model type Jigsaw performing well evidenced by the observation result of teacher activities in cycle I was 83.6 (good) and 90.8 (very good) in cycle II. The observation results of student activities in cycle I was 81.9 (good) and 91,7 (very good) in cycle II; (2) science process skills using cooperative model type Jigsaw was increased evidenced by the thoroughness of students in cycle I 58.3% (less) and 91,7% (very good) in cycle II.